Molecular taxonomy of Indopiptadenia oudhensis (Brandis) Brenan (Leguminosae - Mimosoideae) - A threatened endemic monotypic genus - Dhakad, Ashok Kumar; Pandey, Vijay Vardhan; Kumar, Rahul; Thakur, Ajay; Chandra, Anup; Verma, Praveen Kumar (Current Botany, 2020)
Indopiptadenia oudhensis (Brandis) Brenan is a threatened and an endemic legume forest tree genus of tropical moist deciduous forest of lower foothills of Himalaya. As population status of the species is declining at alarming rate, molecular characterization and germplasm conservation is urgently needed. This is the first attempt to draw its phylogeny based on molecular level and evolutionary closeness with other legumes. Among three barcode genes i.e rbcL, matK and ITS, only rbcLaF-rbcLaR gave satisfactory amplification and proved that rbcL is still working well than other barcode genes and justifies the evolutionary affinities with other legume species. Based on nucleotide homeology, the species is closely related to Prosopis cineraria and demonstrated nucleotide variation at only one site (552; A>G). Based on rbcL gene sequences and phylogeny, its evolutionary linkages found similar to the species placed in subfamilies Mimosaoideae and Caesalpiniodeae. However, researchers working on legume phylogeny clearly mentioned that Indopiptadenia is a part of clade mimosoid of Caesalpinioideae based on morphology. Hence, Indopiptadenia oudhensis may be the connecting species between subfamilies Mimosaoideae and Caesalpiniodeae.